PENERAPAN MODEL CONCEPT SENTENCE DENGAN MEDIA GAMBAR DALAM PENINGKATAN KETERAMPILAN MENULIS KARANGAN PADA SISWA KELAS IV SD NEGERI 1 BUMIREJO TAHUN AJARAN 2014/2015 - Purwanti, Endah (KALAM CENDEKIA PGSD KEBUMEN, 2018)
Abstract: Application of Concept Sentence Model with Picture Media in Improving Essay Writing Skills at The Fourth Grade Students of SDN 1 Bumirejo in The Academic Year of 2014/2015. The purpose of this research to describe the steps of the application of concept sentence model with picture media in improving, to improve essay writing skills. This classroom action research was conducted in three cycles, consisting of planning, implementation, observation, and reflection. The results of the research show that the application of concept sentence model with picture media can improve the essay writing skill. The percentage of completeness was 61.84% in the first cycle, 78.95% in the second cycle, and 94.70% in the third cycle. The conclusion of this research is the application of concept sentence model with picture media can improve the essay writing skills at the fourth grade students of SDN 1 Bumirejo in the academic year of 2014/2015. Keyword: Concept Sentence, Picture Media, Writting Skills Abstrak: Penerapan Model Concept Sentence dengan Media Gambar dalam Peningkatan Keterampilan Menulis Karangan pada Siswa Kelas IV SD Negeri 1 Bumirejo Tahun Ajaran 2014/2015. Tujuan penelitian ini untuk mendeskripsikan langkah-langkah penerapan model concept sentence dengan media gambar, meningkatkan keterampilan menulis karangan serta mendeskripsikan kendala dan solusi penerapan model concept sentence dengan media gambar. Penelitian Tindakan Kelas dilaksanakan dalam tiga siklus terdiri atas perencanaan, pelaksanaan, observasi, refleksi. Hasil penelitian menunjukkan penerapan model concept sentence dengan media gambar dapat meningkatkan keterampilan menulis karangan. Persentase ketuntasan siswa pada siklus I sebanyak 61,84%, siklus II 78,95%, dan siklus III 94,70%. Simpulan penelitian ini adalah penerapan model concept sentence dengan media gambar dapat meningkatkan keterampilan menulis karangan pada siswa kelas IV SDN 1 Bumirejo tahun ajaran 2014/2015. Kata Kunci: Concept sentence, Media Gambar, Keterampilan Menulis